Pelatihan Perancangan Bahan Ajar Matematika Berbasis Kontekstual untuk Guru SMK di Dharmasraya - Armiati, Armiati; Martin, Sri Novia; Mirna, Mirna; Putri, Aprilia Revita; Restu, Dea Aulia (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
Mathematics learning at vocational schools (SMK) should be adjusted to the context and vocation of each so that students can understand mathematics material easily and learning becomes meaningful. However, contextual and vocational-based mathematics teaching materials have not been widely circulated. Therefore, SMK Mathematics teachers must be able to design and make the teaching materials themselves. The purpose of this Community Service activity is to train Mathematics teachers in the Dharmasraya district to be able to design contextual-based Mathematics teaching materials. This activity will be carried out in July and August 2024 in Dharmasraya Regency. This activity was attended by 21 Mathematics teachers of Vocational Schools in Dharmasraya from nine different vocational schools. The activity went smoothly. The teachers participated in the activity with enthusiasm. Based on the results of the satisfaction questionnaire. Participants felt satisfied with the activities carried out. Participants hope that in the future other trainings will also be held that support SMK Mathematics learning.